2010
DOI: 10.1007/s10519-010-9404-7
|View full text |Cite
|
Sign up to set email alerts
|

Aggression, Digit Ratio and Variation in Androgen Receptor and Monoamine Oxidase A Genes in Men

Abstract: Variation in prenatal exposure to androgens is thought to be responsible for some of the individual differences in aggressive behavior among adults. A putative indicator of prenatal testosterone exposure, 2D:4D (the index to ring finger length) ratios have shown a weak correlation with aggression. Variation in sensitivity of the androgen receptor, resulting from polymorphism in the AR gene, is also thought to influence the relative expression of sexually dimorphic traits within each sex, including aggressive b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
59
2
1

Year Published

2011
2011
2015
2015

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 81 publications
(67 citation statements)
references
References 73 publications
(98 reference statements)
4
59
2
1
Order By: Relevance
“…2D and E). Our results are in accordance with other studies which have not found a significant relationship between polymorphism in AR and 2D/4D ratio (Hurd et al 2010;Folland et al 2012). Further studies employing more subjects are needed to clarify these inconsistent findings.…”
Section: Discussionsupporting
confidence: 91%
“…2D and E). Our results are in accordance with other studies which have not found a significant relationship between polymorphism in AR and 2D/4D ratio (Hurd et al 2010;Folland et al 2012). Further studies employing more subjects are needed to clarify these inconsistent findings.…”
Section: Discussionsupporting
confidence: 91%
“…Manning et al (2003) have reported that right 2D:4D and right-left 2D:4D were positively correlated with CAGn in men, and Butovskaya et al, 2012 found a similar relationship between male left 2D:4D and CAGn. These relationships were not replicated by Loehlin et al, (2011), andHurd et al, (2011) in men, but Loehlin et al (2011) reported a significant positive correlation between left 2D:4D and CAGn in women. In addition, Knickmeyer et al (2011), considering 2D:4D in newborns, reported that 2D:4D was not predicted by CAGn or by neonatal levels of testosterone, but that the interaction between CAGn and testosterone was predictive of 2D:4D.…”
Section: Discussionmentioning
confidence: 76%
“…In addition, high sensitivity to testosterone has been reported to be correlated with low 2D:4D (16,17). However, other studies have reported null findings with regard to correlation studies between 2D:4D and sensitivity to androgen (18) and have challenged the correlation between 2D:4D and PT (19). Clearly, we need experimental studies that do not suffer from the limitations associated with correlation data.…”
Section: Correlation Studiesmentioning
confidence: 99%